Competition, Infiltration, and Paradigm Formation: A Survey of the Literary Awards of Taiwan Newspaper Supplement - LIN, Tai Man (Journal of Chinese Literature And Culture 馬大華人文學與文化學刊, 2018)
Abstract When it comes to literature writing in Taiwan, literary supplements (Fukan) printed in company with major newspapers have been considered a dynamical field for literary activities. Bolstered by immense influence of newspaper on mass culture, literary awards hosted by the literary supplements are endowed with tremendous influential status in the literary arena of Taiwan. These awards, involving various calls for different genres and the publication of the award-winning works, directly correlate with the development of literature in Taiwan. This article aims to explore the key roles played by both literary supplements and the literary awards as their orientation has undergone drastic transformation from being led by government policies to market-oriented. Opinions vary in regard to the â€œeffectivenessâ€ of literary awards: while amateur writers made their debuts and successfully entered the literary arena by winning prestigious prizes, and the awards also have helped stimulate creative writing of various genres, effectively broadening the horizon of literature, it is also true that many award entries were specifically written with the intentions of winning the prizes, falling into stereotypes that paradoxically discourage genuine creativity. Taking both perspectives into account, this study tries to re-evaluate the literary awards hosted by newspaper supplements and attempts to explore their different orientations. As literary awards have been recognized as possessing a formative function in shaping the literary paradigm and establishing certain literary trends for contemporary literature in Taiwan, this survey hopes to shed a new light on the formation and the paradigm shift in the literaryfield of Taiwan.